ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PEMBELIAN ULANG (Studi pada Konsumen E-Commerce Shopee di Kota Semarang) - Wibawana, Widhia Arum; Mahfudz, Mahfudz (Diponegoro Journal of Management, 2020)
This study aimed to analyze the factors that influence repurchase intention using utilitarian value, hedonic value, and social value as independent variables, also consumers satisfaction as intervening variables, a study on e-commerce Shopee’s consumers of college students in Semarang City. Non probability sampling is used for sampling. Data was collected from 150 respondents selected using criteria that should have made online purchase of products on e-commerce Shopee at least once. This study used SEM (Structural Equation Model), with AMOS version 23.0. The results show that utilitarian value did not has positive influence on consumers satisfaction and repurchase intention. Meanwhile, hedonic value did not has positive influence on consumers satisfaction, but have positive influence on repurchase interest. Then, social value also did not has positive influence on consumers satisfaction. And consumers satisfaction has positive influence on repurchase intention..